Potential Screening of Bacteriocinogenic-Lactic Acid Bacteria from Mangrove Sediment of Logending Beach for Fisheries Product Preservation - Dyah Fitri Kusharyati; Taruna Dwi Satwika; Afifah Mariana; Anwar Rovik (Universitas Gadjah Mada, 2021)
The meat and fisheries products have high nutritional content which is highly ideal for bacterial growth. Lactic Acid Bacteria (LAB) have several potential advantages as a bio-preservative agent in the food industry because they produce antimicrobial substances against pathogenic bacteria e.g. bacteriocin. Our previous study has succeeded in isolating and characterizing LAB from the mangrove sediments of Logending Beach, Kebumen. This present study aimed to determine the activity of bacteriocinogenic-LAB against food-borne pathogens and their potential for fisheries product preservation. The study consisted of five serial stages, as follows: screening of LAB isolates, cell-free supernatant production and its inhibition activity, extraction of partially purified bacteriocin, bacteriocin confirmation against proteolytic enzymes, and in-vitro test of partially-purified bacteriocin against Listeria monocytogenes, Shigella flexneri, and Salmonella typhi. A total of 25 out of 99 isolates were able to grow on MRSA+1% CaCO3 medium. Initial screening showed that the cell-free supernatant of 14 LAB isolates was able to inhibit the growth of S. thypi, S. flexneri, and L. monocytogenes. There was an increased inhibitory activity of partially purified bacteriocin when compared with the cell-free supernatant which was statistically different (p<0.01). It indicated that the purification was successfully performed. Bacteriocin expressed a lower inhibition against S. typhi than L. monocytogenes and S. flexneri. The ANOVA test showed that each indicator pathogenic-bacterium expresses a very significant sensitivity to the partially purified bacteriocin.